Reflections concerning: ethnographic ethical decisions and neo-liberal monitoring - Neves,Tiago (2018)
Hypothetical, speculative ethical concerns are no match for real situations. As such, this paper argues that there is an unsurpassable gap between planned, prescriptive ethics and real-time, relational, ethnographic decision making. The enforcement of procedural ethics may actually prevent the development of ethnographic work. Also, we critically assess procedural ethics as being not really about ethics, but rather about the risk management embedded in contemporary academia. We organize ethical issues in three political vectors (the ethnographer him/herself, the relationships with the people in the field, and the ethnographic texts), and then offer suggestions for a humanistic research ethics that involves reclaiming the researchers ethical power, enlarging the notion of what is ethical, and accepting that there is a darker side to ethnography. The account offered here is based on the ethnographic experience of Portuguese and Scotland-based researchers.